2013
DOI: 10.1177/1352458513513059
|View full text |Cite
|
Sign up to set email alerts
|

Five-year results from a phase 2 study of oral fingolimod in relapsing multiple sclerosis

Abstract: We present here results at 60 months (M), from the extension component of a phase 2, randomized, placebo-controlled, double-blind, six-month study evaluating oral fingolimod (1.25 mg or 5 mg daily) in relapsing multiple sclerosis. Placebo patients from the core study were re-randomized to fingolimod 1.25 mg or 5 mg in the extension. All patients received 1.25 mg fingolimod after the M24 visit. A total of 140/281 (49.8%) patients completed M60. Fingolimod treatment was associated with a low annualized relapse r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
3
12
2
Order By: Relevance
“…The first interesting data regarding the efficacy of fingolimod (at the dosage of 1.25 or 5 mg/day) versus placebo in reducing the total number of contrast-enhancing lesions (CELs) and annualized relapse rate (ARR) were showed by one Phase II 36-week trial [7] and confirmed by the extension period phase. Recently, the results at 60 months from the extension component of this Phase II study were published [14], confirming previous results and finding a modest rate of disability progression assessed by Expanded Disability Status Scale (EDSS) in those treated for 5 years [14].…”
Section: Studies and Clinical Efficacysupporting
confidence: 68%
“…The first interesting data regarding the efficacy of fingolimod (at the dosage of 1.25 or 5 mg/day) versus placebo in reducing the total number of contrast-enhancing lesions (CELs) and annualized relapse rate (ARR) were showed by one Phase II 36-week trial [7] and confirmed by the extension period phase. Recently, the results at 60 months from the extension component of this Phase II study were published [14], confirming previous results and finding a modest rate of disability progression assessed by Expanded Disability Status Scale (EDSS) in those treated for 5 years [14].…”
Section: Studies and Clinical Efficacysupporting
confidence: 68%
“…The cardiac effects observed in regard to the first dose of fingolimod give no indication of the need to a reassess therapeutic safety. Furthermore, long-term data analyses did not show any significant effects on blood pressure (Izquierdo et al, 2014;Khatri et al, 2011;Kappos et al, 2015;Cohen et al, 2015).…”
Section: Discussionmentioning
confidence: 91%
“…study 2201) show no relevant effects on heart rate, atrioventricular conduction or left ventricular pump function from fingolimod, after treatment for a total duration of 60 months. Regular intake of fingolimod resulted in a stable rise in blood pressure of 2-3 mmHg (Izquierdo et al, 2014). Similarly the TRANSFORMS extension study revealed no new evidence beyond the findings to date after treatment for a total duration of 24 months (Khatri et al, 2011).…”
Section: Extension Studies Results and Cardiovascular Eventsmentioning
confidence: 96%
“…In this context, macular edema (ME) has been identified as a specific adverse event of fingolimod in renal transplant patients [3,4,5,6]. In the phase II core study of fingolimod in multiple sclerosis (MS) and its extensions, two high doses of fingolimod (1.25 and 5.0 mg) were administered and none of the patients developed ME [7,8,9,10]. However, besides several organ-specific adverse events, ME was observed in patients receiving fingolimod during four phase III MS trials (FREEDOMS, FREEDOMSII, TRANSFORMS, and INFORMS) [11,12,13].…”
Section: Introductionmentioning
confidence: 99%